PENDUGAAN AIR TANAH DENGAN METODE GEOLISTRIK TAHANAN JENIS DI DESA TELLUMPANUA KEC.TANETE RILAU KAB. BARRU SULAWESI-SELATAN (Jurnal Geomine, 2015)
Based on the results sheet Pangkajene hydrogeological mapping and Watampone Western (Tjahjadi,B., 1984) shows the potential distribution of groundwater in the Village Tellumpanua District Tanete Rilau Regency Barru South Sulawesi . This study aims to determine the depth and thickness of the aquifer . The study was conducted using geoelectric method sclumberger configuration for measuring the potential difference and current difference as input data determines the apparent resistivity values , further processed by using Software Res2dinv to obtain resistivity values , then interpreted based on data from outcrop . Measurements were made with nine lines in Village Tellumpanua . Results of analysis of data from nine points obtained guess that the potential fresh water is at a depth between 33 to 91.2 meters below sea level with a thickness between 8.2 to 58.2 meters .